Relationship between Nutritional Status and School Achievement of 10-13 Years Old Elementary School Students in Penjaringan 2019 - Christy Venada; Felicia Kurniawan; Isadora Gracia; Yunisa Astiarani (Faculty of Medicine Universitas Padjadjaran, 2021)
Background: School achievement is a crucial element in determining the students’ success. Nutritional status is one of the factors that influence school achievements. This study aimed to analyze the relationship between nutritional status and school achievements among elementary school students.Methods: The cross-sectional analytic observation was conducted during April–November 2019 using a total sampling approach. Four elementary schools in Penjaringan, North Jakarta were chosen and students aged >10 years were selected. The data collected were gender, age, weight, height, and midterm test scores recorded in the school report, including mathematics, science, and Indonesian language. The nutritional status was assessed by body mass index (BMI) and classified upon Permenkes 2 Tahun 2020, which were deficient, sufficient, and overnutrition. Assessment of school achievement based on midterm test scores, categorized according to the 2016 Assessment Guidelines for Elementary Schools (Panduan Penilaian untuk Sekolah Dasar), into three classifications of good, fair, and poor. Data were analyzed using Chi-square. Results: Of the 436 students, 21.8% (n=95) of students were considered good, 28.2% (n=123) were fair, and 50% (n=218) were poor. The nutrition level was deficient in 9.6% (n=42) students, whereas 54.8% (n=239) students had sufficient nutrition, and 35.6% (n=155) students had overnutrition. Bivariate analysis test showed a statistically insignificant relationship between nutritional status and school achievement (p>0.05).Conclusion: This study indicates that nutritional status does not affect school achievement. Further study is needed to determine other factors such as health, intelligence, anxiety, motivation, family, and living environment that may influence school achievement.